Analisis Tahap Perkembangan Wisata Lembah Tumpang Kabupaten Malang Berdasarkan Tourism Area Life Cycle - Malik Fauzi, Hilda; Idris (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2024)
Tumpang Valley Tourism has the potential of a water source that has been developed into a royal conceptualized tourist spot with temple buildings and surrounded by ponds that make the tourist spot feel cool. But even though it has been conceptualized neatly, Tumpang Valley Tourism has a fairly small number of tourist visits. The purpose of this research is to identify attractions, accessibility and amenity which are then analyzed based on tourism area life cycle analysis used to analyze the development stage of Tumpang Valley Tourism so that it can be used in formulating tourism development strategies. The research method is to use a qualitative approach and case study research design, while collecting data through observation, interviews and documentation with a case study research design. In analyzing the data using Butler's TALC theory. The results showed that the attraction conditions were quite numerous and interesting, while the accessibility conditions were quite easy but there were several points of the road that were starting to break down. And for the condition of the amenity is quite complete and supports the needs of tourists. Then the development stage of Tumpang valley tourism based on TALC theory is at the development stage which is marked that the dominant tourism components lead to the characteristics of the development stage. Thus, stakeholders need to pay attention to tourism maintenance for the comfort and safety of visitors.